2017
DOI: 10.1016/j.omtn.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Next-Generation BET-Independent MLV Vectors for Safer Gene Therapy

Abstract: Retroviral vectors have shown their curative potential in clinical trials correcting monogenetic disorders. However, therapeutic benefits were compromised due to vector-induced dysregulation of cellular genes and leukemia development in a subset of patients. Bromodomain and extraterminal domain (BET) proteins act as cellular cofactors that tether the murine leukemia virus (MLV) pre-integration complex to host chromatin via interaction with the MLV integrase (IN) and thereby define the typical gammaretroviral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 79 publications
3
35
0
Order By: Relevance
“…This could be studied using the BET-independent gammaretroviral vectors that integrate outside the active TSS and enhancers [ 20 , 21 ]. In this context, a recent study [ 22 ] reported that the next-generation BET-independent MLV-derived vectors showed the same stability of expression without genotoxicity when compared to a wild-type MLV-derived vector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be studied using the BET-independent gammaretroviral vectors that integrate outside the active TSS and enhancers [ 20 , 21 ]. In this context, a recent study [ 22 ] reported that the next-generation BET-independent MLV-derived vectors showed the same stability of expression without genotoxicity when compared to a wild-type MLV-derived vector.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the interaction between the intasome and BET proteins or LEDGF/p75 has resulted in the decreased efficiency of retrovirus integration and retargeting outside the preferred genomic regions [ 12 , 20 ]. Hence, retargeting strategies are already being used to design the next generation of retroviral vectors [ 20 , 21 , 22 ] that demonstrate the decreased risk of cellular protooncogene transactivation [ 23 ]. In addition to genetic manipulation of retroviral integrase, specific HIV-1 integrase-LEDGF/p75 interaction can also be allosterically inhibited with small molecules of LEDGF/p75 inhibitors (LEDGINs), which represents a new and promising therapeutic strategy [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that removing the TP was insufficient to redirect all integrations away from active promoters and strong enhancers, or to eliminate the stochastic events that can select for oncogenic activation. Ultimately, a modified vector that combines SIN LTRs to eliminate strong viral enhancers [10,81] with insertions/replacement of the IN TPto redirect integration to less active regions [39,82] could decrease vector genotoxicity and overcome current limitations for clinical applications.…”
Section: In Tp-vectors For Gene Therapymentioning
confidence: 99%
“…Subsequent approaches involving self-inactivating (SIN) vectors [38] or lentiviral vectors have been used to address these outcomes [30]. Alternatively, addressing the integration target-site bias of gammaretroviruses to integrate preferentially at promoter/enhancer regions by altering or eliminating their interaction with host BET protein could alter the oncogenic potential of these vectors [4,39].…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 , 12 , 13 , 14 , 16 , 18 Based on these findings, several trials, often involving viral integrase engineering, have been conducted to alter the retroviral integration patterns by interfering with the interactions between the cellular tethering factors and the virus, or by conferring viruses the ability to interact with new host proteins. 20 , 21 , 22 , 23 In particular, MLV integrations around TSSs have been successfully reduced, but still occur at significantly high frequencies, indicating that there might be other, unknown mechanisms underlying the integration process. 20 However, searching the complete MLV integration mechanisms and finding ways to block all the critical mechanisms require substantial time and effort.…”
Section: Introductionmentioning
confidence: 99%